1995
DOI: 10.1128/jcm.33.8.1997-2001.1995
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of commercial antisera for Shigella serogrouping

Abstract: Shigella serogrouping antisera from six companies (Becton Dickinson, Denka, Difco, Murex, Roach, and Sanofi-Pasteur) intended for the slide agglutination test and those of the Wellcolex Colour Shigella latex agglutination test were evaluated to identify quality products for Shigella identification. Forty-six reference Shigella strains (one for each serotype and species), 50 clinical strains (21 S. flexneri, 21 S. sonnei, 4 S. dysenteriae, 4 S. boydii) representing the most prevalent species and serotypes encou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Conventional Shigella identification method is labor-intensive, potentially subjective, and not sufficiently accurate. Using molecular profiling, we showed that conventional Shigella serotyping was at best 90% accurate, consistent with a previous report of an upper limit at 91% (17). Similarly, biochemical identification could erroneously assign some Shigella isolates as E. coli.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Conventional Shigella identification method is labor-intensive, potentially subjective, and not sufficiently accurate. Using molecular profiling, we showed that conventional Shigella serotyping was at best 90% accurate, consistent with a previous report of an upper limit at 91% (17). Similarly, biochemical identification could erroneously assign some Shigella isolates as E. coli.…”
Section: Discussionsupporting
confidence: 87%
“…Serological differentiation is essential but is laborious, time-consuming, and expensive and can be erroneous. Intra-and interspecies cross-reactivity is common, and commercial antisera are at best 91% accurate (17). Rough strains that do not express O antigen and newly emerged Shigella serotypes without antisera that recognize them are nontypeable, accounting for 6 to 10% of annual Shigella isolates in the United States (8).…”
mentioning
confidence: 99%
“…[10][11][12][13] Campylobacter isolates were further speciated using hippurate hydrolysis, 14 and Shigella isolates were serogrouped and serotyped by slide agglutination using commercial antisera (Difco Laboratories, Livonia, MI). 15 In addition, five E. coli-like colonies were picked and tested for the expression of heat-labile enterotoxin (LT) and/ or heat-stable enterotoxin (ST) using a GM1 ELISA. 16,17 Colonies testing positive for LT or ST were further tested for expression of colonization factor (CF) antigens CFA/I, CFA/ II (coli surface antigen [CS] 1, CS2, CS3), CFA/III, CFA/IV (CS4, CS5, CS6), CS7, CS17, PCFO159, and PCFO166 by monoclonal antibody dot blot assay.…”
Section: Study Sitesmentioning
confidence: 99%
“…Confirmatory identifications were performed with API-20E test kits used according to the instructions of the manufacturer (Bio-Merieux Vitek Inc., Hazelwood, Mo.). Serogroups and serotypes were determined by visual inspection of slide agglutination assays, with commercial antisera used as described by the manufacturer (Difco Laboratories) (10). Briefly, strains were subcultured on tryptic soy agar (Difco) and tested for agglutination on glass slides.…”
mentioning
confidence: 99%
“…These serologically atypical strains displayed conflicting agglutination patterns, reacting strongly with serotype 1-specific antisera but also weakly with serotype 4-specific antisera. These equivocal results may reflect the limitations of available commercial antibody reagents to reliably detect the full diversity of serologic variants of S. flexneri (8,10).…”
mentioning
confidence: 99%